Assessing and Analysing Value Added by Private Equity/Venture Capital Firms to Portfolio Companies - El Shaarawy, Haytham (2011)
The idea of private equity (PE) and/or venture capital (VC) is under an on-going debate, especially when it comes to “adding value” to portfolio firms. Researches find PE/VCs have great contributions to the value of their portfolios. However, there is no definite consensus on the way PE/VCs add value to portfolio companies. Literature suggested many factors influencing value, yet, minimal quantified. Based on a sample size of 1,061 buyout transactions in the UK market over the period 1970–2010, this research will use proxies for measuring value adding inputs and output through two multiple regression models. Overall, results were not very conclusive, yet, for some variables, results of the analysis were coherent with the literature and also gave good indications for the direction and magnitude of relations between some of the suggested variables and the value added proxy. Accordingly, this research will try to contribute to the existing literature through an attempt to shape and quantify some of the previous research suggested factors which add value to firms, while presenting the theory behind them.